PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN AKHLAK SISWA MELALUI TIKTOK - Muhammad Ivansyah; Muzammil (LPPM STAI Muhammadiyah Probolinggo, 2025)
TikTok as a social media platform is increasingly popular among students and has the potential to be a learning medium. This study aims to analyse the use of TikTok in shaping students' morals and improving their understanding of Islamic values at Tarbiyatul Wathon Islamic Elementary School. This study uses a qualitative approach with a case study research method, collecting data through observation, in-depth interviews with teachers, and content analysis of TikTok used in Islamic education learning. The results showed that the use of TikTok in Islamic education can increase student engagement and strengthen their understanding of Islamic teachings through engaging educational content. However, challenges such as distraction and access to inappropriate content remain a concern. This study emphasises that the role of Islamic education teachers is crucial in controlling and guiding the use of social media to keep it in line with Islamic values. Further research is recommended to explore the long-term impact of using TikTok in Islamic character education.